The treatment of wastewater containing pharmaceuticals in microcosm constructed wetlands: the occurrence of integrons (int1-2) and associated resistance genes (sul1-3, qacEΔ1) - Nowrotek, Monika; Kotlarska, Ewa; Łuczkiewicz, Aneta; Felis, Ewa; Sochacki, Adam; Miksch, Korneliusz (Environmental science and pollution research international, 2017)
The aim of this study was to analyze the occurrence of sulfonamide resistance genes (sul1-3) and other genetic elements as antiseptic resistance gene (qacEΔ1) and class 1 and class 2 integrons (int1-2) in the upper layer of substrate and in the effluent of microcosm constructed wetlands (CWs) treating artificial wastewater containing diclofenac and sulfamethoxazole (SMX), which is a sulfonamide antibiotic. The bacteria in the substrate and in the effluents were equipped with the sul1-2, int1, and qacEΔ1 resistance determinants, which were introduced into the CW system during inoculation with activated sludge and with the soil attached to the rhizosphere of potted seedlings of Phalaris arundinacea 'Picta' roots (int1). By comparing the occurrence of the resistance determinants in the upper substrate layer and the effluent, it can be stated that they neither were lost nor emerged along the flow path. The implications of the presence of antibiotic resistance genes in the effluent may entail a risk of antibiotic resistance being spread in the receiving environment. Additionally, transformation products of SMX were determined. According to the obtained results, four (potential) SMX transformation products were identified. Two major metabolites of SMX, 2,3,5-trihydroxy-SMX and 3,5-dihydroxy-SMX, indicated that SMX may be partly oxidized during the treatment. The remaining two SMX transformation products (hydroxy-glutathionyl-SMX and glutathionyl-SMX) are conjugates with glutathione, which suggests the ability of CW bacterial community to degrade SMX and resist antimicrobial stress.
Keywords: Treatment wetlands; mokřady; Waste Water; Integrons; Anti-Bacterial Agents; odpadní voda; integrony; antibiotická rezistence; biodegradace; Biodegradation, Environmental; Transformation products; Wetlands; Antibiotic resistance genes; léčivé přípravky; Pharmaceuticals; Wastewater; antibakteriální látky; Pharmaceutical Preparations; Drug Resistance, Microbial